What are the Lessons that can be Drawn from International Experience on Sustainable Transport for Johannesburg? Case Study: Berlin, Germany - Ngoma, Ralph Thabiso (University of the Witwatersrand, Johannesburg, 2024)
This study unravels the performance of sustainable transport in two vastly different and unique spatial contexts, which have developed from comparable historical landscapes. The transport performance in the city of Johannesburg, South Africa and the city of Berlin, Germany is assessed respectively, to note the effectiveness of the transport modes individually and collectively. It is not a comparative study, but rather a study seeking to understand the actualisation of the concept ‘sustainable transport’ in Johannesburg. The problem statement is asking how the nuanced applicability of sustainability in transport can inform transport plans. The nuanced applicability of sustainability must inform transport plans, so that the vision of sustainable transport is strategically applied in the Johannesburg city plans and those of the other cities in the global south. There is a set of criteria that was adapted to assess the performance of transport in the respective cities, thereby extracting valuable lessons for Johannesburg. The qualitative method of study was used to gather the required data, through case studies, desktop research and unstructured discussions. The report argues for innovative and context sensitive approaches to conceptualising sustainable transport in the cities of the global south, and this is informed by the growth strategy of the respective cities. It is noted that transport and land use are co-dependent, therefore sustainable cities are those that integrate all the elements of sustainability in development plans. The results speak to planners and policy makers to have a nuanced view of transport, thus developing forward-looking frameworks to address sustainability as postulated by UN Habitat goals. The goal is to improve mobility in the city and keep abreast with new innovative approaches to unpacking ‘sustainable transport’ in literature, to inform the ever-growing sustainable, resilient and inclusive cities of the global south.
A Research Report submitted to the Faculty of Engineering and Built Environment in fulfilment of the degree, Master of Science in Development Planning, School of Architecture and Planning, University of Witwatersrand, Johannesburg, in 2024.
Keywords: Sustainable Transport; Sustainable development; Transit oriented development; Compaction; Densification; Motorised transport; Non motorised transport; UN Habitat goals; Sustainble Development Goals (SDGs); SDG-11: Sustainable cities and communities; SDG-17: Partnerships for the goals